PERBANDINGAN HASIL ULANGAN HARIAN MATA PELAJARAN PJOK (DENGAN PROGRAM MBG) PADA SISWA SD INPRES RABIAJALA KAB KEPULAUAN ARU DAN SD INPRES KINALI KAB MINAHASA - Mautang, Hizkia Gymnastic (Yayasan Syalom Cipta Sumikolah, 2024)
This study aims to compare the daily test results of Physical Education, Sports, and Health Education (PJOK) between students of SD Inpres Rabiajala in the Kepulauan Aru Regency, located in the 3T (Underdeveloped, Frontier, and Outermost) area, and SD Inpres Kinali in the Minahasa Regency, located in self-sufficient area, with consideration of the differences in the implementation of the Free Nutritious Meal Program (MBG) in both schools. This research uses a quantitative approach with a comparative design, where the research sample is taken using purposive sampling, specifically sixth-grade students from both schools. Data was collected using the documentation method to obtain the daily test results of PJOK. The findings showed that the average daily test score of students from SD Inpres Rabiajala was 80.62, while SD Inpres Kinali obtained an average score of 85.34. Hypothesis testing using the t-test formula resulted in a t-value of -2.86154, which is lower than the t-table value (2.000), indicating that H0 is rejected and there is a significant difference between the two schools. This finding suggests that the Free Nutritious Meal Program has a significant impact on the PJOK daily test results, thereby reinforcing the importance of the sustainability of nutrition programs in schools to support students' academic achievement and health. This research is expected to provide insights for educational policy, particularly in integrating nutrition as a supporting factor for student learning success.